Efficacy and Safety of Erythromycin in the Treatment of Mycoplasma Pneumonia in Children: A Systematic Review and Meta-Analysis - Sun, Mingxiu; Xue, Zhirui; Li, Jiarui; Du, Likun (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim The effectiveness and safety of erythromycin for treating mycoplasma pneumonia in pediatric patients is a subject of significant interest. This study aims to conduct a systematic review and meta-analysis to assess the efficacy and safety of erythromycin in the treatment of mycoplasma pneumonia in children,with the goal of providing evidence-based recommendations for pediatric care. Methodology We systematically reviewed randomized controlled trials published prior to January 1, 2024, that evaluated the efficacy and safety of erythromycin in the treatment of mycoplasma pneumonia in children. Outcome measures of primary concern include clinical efficacy, complications or adverse events. We used the inverse variance method to perform a meta-analysis of random effects, representing the effects in terms of Standardized Mean Difference (SMD) or Mean Difference (MD) and giving a 95% Confidence Interval (CIs). In addition, we performed a risk assessment of bias using the Cochrane tool. A total of 68 relevant studies were searched and 4 literatures meeting the requirements were included, with a total of 599 children. Results The results of meta-analysis showed that the efficacy of erythromycin in the treatment of mycoplasma pneumonia in children was not statistically significant compared with conventional treatment [RR=12.31, 95%CI (-1.23, 25.86)]. The safety of erythromycin in the treatment of mycoplasma pneumonia in children was significantly different from that of conventional treatment [RR=5.55, 95%CI (2.65, 11.65)]. Subgroup analysis showed that the meta-analysis results of the three literatures showed RR=1.95, 95%CI (1.01,3.74), suggesting that there was no statistically significant difference between the two groups of children with diarrhea. The results of meta-analysis of the two literatures showed that RR=1.95, 95%CI (0.63, 6.04), indicating that there was no statistical significance in the difference between the two groups of children with abdomina. The results of meta-analysis of the two literatures showed that RR=3.95, 95%CI (1.62, 5.58), indicating that there was a statistically significant difference between the two groups of pain children. The results of trial sequence analysis showed that the results of clinical efficacy and safety were considered reliable and stable and the safety of the experimental group was better than that of the control group in the treatment of pediatric mycoplasma pneumonia. Conclusion Erythromycin is effective and safe in the treatment of mycoplasma pneumonia in children. Due to individual differences and the severity of the disease, there are certain differences in clinical treatment effects and some adverse reactions and drug resistance problems also need to be paid attention to and solved.
Keywords: Erythromycin; Mycoplasma pneumonia in children; Clinical efficacy; Safety; Meta-analysis; Systematic evaluation